Turkish Staatsvolk vs. Kurdish identity: Denial of the Kurds in Turkish school textbooks. Issue 4 (1st October 2016) - Yanarocak, Hay Eytan Cohen
ABSTRACT: Under Mustafa Kemal Atatürk, the Turkish nation-state sought to Turkify all of its non-Turkic minorities. His well-known motto of "How happy is the one who says I am a Turk" became the slogan of this policy. The Treaty of Lausanne (1923) that provided the ultimate legitimacy for the Turkish nation-state drew the lines of sociological borders in the newborn republic. This study highlights the denial of Kurdish identity in Turkish school textbooks. Since national indoctrination was carried out through the textbooks used in three core courses — Civics ( Vatandaşlık ), History ( Tarih ), and National Security Studies ( Milli Güvenlik Bilgisi ) — this research will attempt to trace this policy of denial by examining relevant chapters in these volumes that were published in the 1924–2002 period. While doing that, the article will focus on the 1980–2002 period since, in that given time interval, the Turkish state not only ignored the Kurdish identity but also actively denied its existence. In order to remain in the historical timeframe, the research limits its scope to the rise of the AKP in 2002.